A deterministic model-based contact analysis of Gaussian and non-Gaussian rough surfaces using finite element method. (1st January 2013) - Megalingam Murugan, A.; Mayuram, M.M.
Rough surfaces having skewness values of –0.3, 0 and +0.3 and kurtosis ranging from two to four, are developed using FFT and analysed using FEM based ANSYS package. The continuity of elastic, elasto-plastic and plastic deformations of near realistic feature-based asperities and effects of asperity interactions are inherently included in the present deterministic contact approach. The results showed that the rough surface having positive skewness leads to minimum area of contact but attains the maximum value of mean contact pressure ( Pmean ) earlier and consequently can lead to severe wear when compared with Gaussian and negatively skewed surfaces. The area of contact and contact load decrease whereas the Pmean increases with an increase in kurtosis value. In the platykurtic surfaces, the contact load is shared by most of the contacting asperities and the neighbouring asperity interactions restrain the asperities to remain in elastic state mostly even at high loads. ASME Journal of Tribology, Wear, Materials Letters and Tribology International .